2001
DOI: 10.1021/jf001147c
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Rice Bran for Removal of Organochlorine Compounds and Benzene from Industrial Wastewater

Abstract: Rice bran was found to effectively adsorb several organic compounds, such as dichloromethane, chloroform, carbon tetrachloride, trichloroethylene, tetrachloroethylene, and benzene. Equilibrium adsorption isotherms conformed to the Freundlich type (log-log linear). The adsorption of dichloromethane and chloroform by rice bran was observed over the range of pH 1-11. Therefore, rice bran is applicable for treatment of wastewater over a wide pH range. Dichloromethane was successfully removed from water samples wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…1,2) Furthermore, it was confirmed that the spherosomes isolated from these adsorbents were effective in removing these organic compounds. 1,2) Analytical and laser microscopic data have confirmed that the removal of organochlorine compounds and benzene is dependent on the uptake of these compounds into intracellular particles called spherosomes.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…1,2) Furthermore, it was confirmed that the spherosomes isolated from these adsorbents were effective in removing these organic compounds. 1,2) Analytical and laser microscopic data have confirmed that the removal of organochlorine compounds and benzene is dependent on the uptake of these compounds into intracellular particles called spherosomes.…”
Section: Introductionmentioning
confidence: 82%
“…1,2) Analytical and laser microscopic data have confirmed that the removal of organochlorine compounds and benzene is dependent on the uptake of these compounds into intracellular particles called spherosomes. 1,2) Spherosomes are widely distributed among plants and fungi but have not been observed in animal cells.…”
Section: Introductionmentioning
confidence: 99%
“…1) Furthermore, it was confirmed that the spherosomes isolated from these adsorbents were effective in removing these organic compounds. 2) Analytical and laser microscopic data have confirmed that the removal of organochlorine compounds and benzene is dependent on the uptake of these compounds into intracellular particles called spherosomes.…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, it was confirmed that the spherosomes isolated from rice bran were effective in removing these organic compounds. 10) Analytical and laser microscopic data have confirmed that the removal of organochlorine compounds and benzene is dependent on the uptake of these compounds into intracellular particles called spherosomes. 10) Spherosomes are intracellular particles about 10 µm in diameter and widely distributed among plants and fungi.…”
Section: Adsorption Mechanismmentioning
confidence: 98%
“…10) Analytical and laser microscopic data have confirmed that the removal of organochlorine compounds and benzene is dependent on the uptake of these compounds into intracellular particles called spherosomes. 10) Spherosomes are intracellular particles about 10 µm in diameter and widely distributed among plants and fungi. 11) Neither the function of spherosomes nor its analysis is well understood.…”
Section: Adsorption Mechanismmentioning
confidence: 98%